The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2002
DOI: 10.1590/s0100-204x2002000400020
|View full text |Cite
|
Sign up to set email alerts
|

Physical and chemical characteristics of sapota fruit at different stages of maturation

Abstract: In the present work, the physical and chemical characteristics in three stages of maturation of sapota (Manilkara zapota L.P. Royen) fruit were studied as well as its post-harvest behavior during storage at ambient and refrigerated conditions. With the advance of maturation, the concentration of the reducing sugars increased while the total acidity and tannin contents decreased. The fruits which did not have their pedicel removed during the post-harvest presented the storage time superior when compared with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
1
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 2 publications
3
26
1
2
Order By: Relevance
“…7). The similar trend was observed when fruit ripens the pH value increases and when it was over ripened the pH value decreases due to turning sour to fermentation sugars (Mohamed et al, 1996;Brito and Narain, 2002). The increased trend of pH value was due to decrease in acidity and increase in soluble sugars during ripening.…”
Section: Chemical Parameters Of Sapota Qualitysupporting
confidence: 64%
See 2 more Smart Citations
“…7). The similar trend was observed when fruit ripens the pH value increases and when it was over ripened the pH value decreases due to turning sour to fermentation sugars (Mohamed et al, 1996;Brito and Narain, 2002). The increased trend of pH value was due to decrease in acidity and increase in soluble sugars during ripening.…”
Section: Chemical Parameters Of Sapota Qualitysupporting
confidence: 64%
“…Acidity of Sapota decreased from 1.92-0.74 in control while that decreasing trend exists in the aloe-pectin treated Sapota also but less than that of control ( Fig.8) (Brito and Narain, 2002;. The TA was decreasing due to increase of soluble sugars during the course of ripening (Abbas and Fandi, 2002).…”
Section: Titrable Aciditymentioning
confidence: 80%
See 1 more Smart Citation
“…Total soluble solid content decrease with age, where the highest was found during the half-ripe stage, and the lowest was found during the fully ripen stage (Pawar, 2011). The o Brix value of the sapodilla fruit could reach as high as 21.40 during the half-ripe stage and as low as 15.80 during the fully ripened stage (Brito and Narain, 2002).…”
Section: Total Soluble Solid Contentmentioning
confidence: 95%
“…The titratable acidity was calculated on the basis of citric acid because citric acid is the major organic acids in the sapodilla fruit (Lee et al, 2013). The titratable acidity of the sapodilla fruit was found to peak during its mature green stage (5.89%) and the lowest value was found during the overripe stage (4.95%) (Brito and Narain 2002). Kulkarni et al (2007) reported that sapodilla juice contained 0.16% of titratable acidity, which was calculated on the basis of citric acid.…”
Section: Titratable Aciditymentioning
confidence: 99%